Characteristics of Surface Runoff for Four Vegetation Types in Small Watershed of Nver Zhai in West Hunan, China (Bangladesh Journal of Botany, 2021)
Characteristics of the surface runoff of four vegetation types in the small watershed of Nver Zhai, Wuling Mountain Area, West Hunan were studied. Results indicated that, from June 10, 2015 to September 10, 2016 the precipitation recorded was up to 1971.80 mm, and there occurred 83 rainfalls during the period of investigation. With the increase in the rainfall, the surface runoff gradually increased, among which the Eucommia ulmoides Oliv. plantation showed significantly high runoff. When the rainfall gradually increased to 30 mm, the surface runoff was highest for the sloping farmland. Under an intense rainfall >50 mm, there was a significant augmentation in the surface runoff of the four types of forest lands, indicating that the soil water content began to reach to saturation. Furthermore, the total runoff of the different types of vegetation, the runoff depth and the runoff coefficient were in the order of: E. ulmoides plantation > Pinus massoniana Lamb. forest > Sloping farmland > maple- Cinnamomum camphora (L.) J. Presl. mixed plantation. Additionally, under the same rainfall, there was a reduction in the runoff with an increase in the evaporation, and the total runoff of maple- C. camphora mixed plantation was the lowest.Bangladesh J. Bot. 50(3): 603-611, 2021 (September)